The Changes in the Functional Urban Region in the New Socio-Economic Conditions in Poland. The Case of Toruń - Hołowiecka, Beata; Szymańska, Daniela (Bulletin of Geography. Socio-economic Series, 2008)
This article attempts to determine the general tendency of changes of functioning of urban regions in the new socio-economic conditions in Poland. The functional connections resulted from an intensively and relatively permanent flow of population, which functions as foundation of identification of the urban region in that study. The paper presents the results of empirical examinations of the functional urban region of Toruń conducted in 70s, 80s, and presently. On that basis explation is presented on how the transformation of the economic system with all consequences influenced on the modification of developed and relatively stable city-surroundings relations. Additionally the article is aimed at recognizing the new determinants of urban regions development in Polish conditions.